Quality of bovine colostrum and its relation to genetics, management, physiology and its freezing - Glombowsky P.* (2020)
© The Author(s), Journal MVZ Cordoba 2020.Objective. The aims of this study were to assess whether colostrum quality is modified by genetic, physiological and management characteristics in the pre-partum period, as well as evaluate whether quality and composition of colostrum is altered in the freezing process. Material and methods. In the experiment I, colostrum and blood samples of 35 cows (18 Holstein and 17 Jerseys) were collected. In the experiment II, six colostrum samples of Holstein cows were collected and frozen during 60 days. Results. The mean immunoglobulin (Ig) concentration was 77.65 mg/ml to Jersey and 82.77 mg/ml to Holstein. The genetic, parturition order, and the interaction between these factors were no significant on IgG concentration in the colostrum. Also, it was observed an effect genetic of cow in the weight on calf at birth and on three days of age (p<0.0001). Regarding transmission of calf passive immunity, no effects of cow breed and calving order were observed on plasma protein concentration of calf, as well as after three days of freezing. Calves of Holstein (83%) and Jersey (82%) breed showed total serum protein levels above 5.5 g/dL. Holstein cows housed in individual paddocks with diet supplementation provided better quality of colostrum (93.57 mg Ig/mL). Over time, the percentage of fat reduced at freezing, that reduced over time (p<0.05) in Experiment II. Conclusions. The pre-partum management exerts influence on colostrum quality, and the freezing not interfere on centesimal and immunological quality of colostrum, with exception the fat, that decrease along the time.